Structure‐Based Design of Microsomal Prostaglandin E2 Synthase‐1 (mPGES‐1) Inhibitors using a Virtual Fragment Growing Optimization Scheme. (24th February 2016) - Lauro, Gianluigi; Tortorella, Paolo; Bertamino, Alessia; Ostacolo, Carmine; Koeberle, Andreas; Fischer, Katrin; Bruno, Ines; Terracciano, Stefania; Gomez‐Monterrey, Isabel Maria; Tauro, Marilena; Loiodice, Fulvio; Novellino, Ettore; et al.
Abstract: A small library of 2, 3‐dihydroxybenzamide‐ and N ‐(2, 3‐dihydroxyphenyl)‐4‐sulfonamide‐based microsomal prostaglandin E2 synthase‐1 (mPGES‐1) inhibitors was identified following a step‐by‐step optimization of small aromatic fragments selected to interact in focused regions in the active site of mPGES‐1. During the virtual optimization process, the 2, 3‐dihydroxybenzamide moiety was first selected as a backbone of the proposed new chemical entities; the identified compounds were then synthesized and biologically evaluated, identifying derivatives with very promising inhibitory activities in the micromolar range. Subsequent structure‐guided replacement of the 2, 3‐dihydroxybenzamide by the N ‐(2, 3‐dihydroxyphenyl)sulfonamide moiety led to the identification of N ‐(2, 3‐dihydroxyphenyl)‐4‐biphenylsulfonamide (6 ), the most potent small molecule of the series (IC50 =0.53±0.04 μm ). The simple synthetic procedure and the possibility of enhancing the potency of this class of inhibitors through additional structural modifications pave the way for further development of new molecules with mPGES‐1‐inhibitory activity, with potential application as anti‐inflammatory and anticancer agents. Abstract : mPGES‐1 inhibitors were selected using a virtual fragment growing strategy. The most active compound (6 ) inhibits mPGES‐1 in the low micromolar range. The reported results highlight the possibility of obtaining new enhanced compounds through simple chemical modifications.